Forbedring af datatilgang i elektroniske opslagsværker i forbindelse med kognitive brugersituationer - Ptaszynski, Marcin Overgaard (Nordiske Studier i Leksikografi, 2010)
It would not be incorrect to claim that besides developing theories and methodologies that can improve the compilation of needs adapted reference works, the ultimate objective of lexicography is to offer the user of a reference work quick and easy access to data which satisfy his need for information. Therefore, access to data should reflect the user’s needs which appear in specific extra-lexicographical situations. This article offers an investigation of access to data in electronic reference works which aim to satisfy the needs that appear in the so-called cognitive situations (cf. Tarp 2006: 57 ff.). The analysis focuses on forms of access that hitherto rarely have been discussed by lexicographers. On its basis it is concluded that access to data can be and should be improved. This requires both a redefinition of the term access and a more efficient implementation of available technological solutions.